1998
DOI: 10.1093/milmed/163.8.568
|View full text |Cite
|
Sign up to set email alerts
|

Cold Weather Injuries in an Arctic Environment

Abstract: The cases of eight Special Forces soldiers who sustained cold weather-related injuries while conducting winter training as part of Operation Arctic Saber in the Northwest Territories and Arctic Circle are reported. Environmentally related injuries can represent difficult diagnostic and treatment challenges in the field. Moreover, they may compromise the overall mission if they are not identified and treated early. Cold weather injuries can also result in long-term disfigurement and disability that may limit a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Extreme weather conditions may affect soldiers who spend a larger portion of their day unsheltered in extreme cold or heat. Weather related injuries can have long-lasting effects on soldiers involving disfigurement and disability [ 153 ]. However, most weather related skin injuries may be avoided with education, proper use of protective clothes and footwear [ 111 , 154 ].…”
Section: Extreme Weather Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme weather conditions may affect soldiers who spend a larger portion of their day unsheltered in extreme cold or heat. Weather related injuries can have long-lasting effects on soldiers involving disfigurement and disability [ 153 ]. However, most weather related skin injuries may be avoided with education, proper use of protective clothes and footwear [ 111 , 154 ].…”
Section: Extreme Weather Conditionsmentioning
confidence: 99%
“…Frostbite is a common cold injury in military soldiers and most commonly affects the digits, ears, nose, and facial skin. Often, the severity of frostbite injury is not evident until a day or two after warming the tissue [ 153 ]. Other common cold weather injuries in military soldiers include immersion foot, pernio, Raynaud phenomenon, and cold urticaria [ 156 ].…”
Section: Extreme Weather Conditionsmentioning
confidence: 99%
“…Previous cold environment military studies have concentrated on energy expenditure and energy balance [ 7 , 16 , 17 ], protective clothing [ 18 ] and cold weather injuries [ 19 ]. Nykänen et al [ 17 ] has recently reported results of the present study population and setting regarding energy balance and changes in body composition.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Varnado's case examples remind us of the need to assess features of development that are pertinent to helping patients adapt these important preventive interventions. Patient education may include consuming a high-protein, high-calorie diet to promote healing, smoking cessation, infection prevention, moisture control, and prevention of maceration between frostbitten digits, regaining range of motion of the affected body part.…”
mentioning
confidence: 99%